Relevansi Hak Asasi Manusia dengan Teori Ahliyyah - Moh Bagus; Siti Partiah (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2020)
Human Rights are the basic rights of humans that inherent to them since they were born. As a constitutional state, Indonesia has legally recognized the existence of those regulations as mentioned in the 1945 Constitution of the Republic of Indonesia. On the other hand, as religion, Islam also has an expert theory or ahliyyah (the appropriateness of someone to act and take responsibility for his or her actions). The purpose of this paper is to find out the relevance of human rights to the expert theory or ahliyyah. By using descriptive normative analysis, it can be concluded that human rights and expert theory have relevance, where the theory of ahliyyah al-wujub had been given before someone was born and the theory of Ahliyyah al-ada’ has newly been given when they are capable or mature. In this case, human rights were given when he or she was born into the world. Of course, this connection is important because Indonesia makes Islamic law as one of the sources in the formation of legislation.